Specific T-cell subsets have a role in anti-viral immunity and pathogenesis but not viral dynamics or onwards vector transmission of an important livestock arbovirus - Newbrook, Kerry; Khan, Nakibul; Fisher, Aimee; Chong, Karen; Gubbins, Simon; Davies, William C.; Sanders, Christopher; Busquets, Marc Guimerà; Cooke, Lyndsay; Corla, Amanda; Ashby, Martin; Flannery, John; et al. (Frontiers in Immunology, 2024)
Bluetongue virus (BTV) is an arthropod-borne Orbivirus which is almost solely transmitted by Culicoides biting midges and causes a globally important haemorrhagic disease, bluetongue (BT), in susceptible ruminants. Infection with BTV is characterised by immunosuppression and a substantial lymphopenia at peak viremia in the host. In this study, the role of cell-mediated immunity and specific T cell subsets in BTV pathogenesis, clinical outcome, viral dynamics, immune protection and onwards transmission to a susceptible Culicoides vector are defined in unprecedented detail for the first time, using an in vivo arboviral infection model system that closely mirrors natural infection and transmission of BTV. Individual circulating CD4 + , CD8 + or WC1 + γδ T cell subsets in sheep were depleted through administration of specific monoclonal antibodies. The absence of cytotoxic CD8 + T cells were consistently associated with less severe clinical signs of BT, whilst the absence of CD4 + and WC1 + γδ T cells both resulted in an increased clinical severity. The absence of CD4 + T cells also impaired both a timely protective neutralising antibody response and the production of IgG antibodies targeting BTV non-structural protein, NS2, highlighting that the CD4 + T cell subset is important for a timely protective immune response. T cells did not influence viral replication characteristics, including onset/dynamics of viremia, shedding, or onwards transmission of BTV to Culicoides. We also highlight differences in T cell dependency for the generation of immunoglobulin subclasses targeting BTV NS2 and the structural protein, VP7. This study identifies a diverse repertoire of T cell functions during BTV infection in sheep, particularly in inducing specific antiviral immune responses and disease manifestation and will support more effective vaccination strategies.